Gradient synergistic fire resistant cable and method of manufacture
Patent Information
- Application Number
- CN202611471826.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-30
AI Technical Summary
为提升高温机械性能,现有耐火电缆多采用纯不锈钢丝编织作为增强层,其虽能提供充足的径向箍紧力,但金属材料导热系数高,在842℃火焰中会快速向内部导体传导热量,加速绝缘层性能衰减;同时在高压线路完整性测试中,若外侧陶瓷壳体局部碎裂,裸露的金属丝易与内部导体接触引发短路,介电安全性不足
Smart Images

Figure CN123017622A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of wire and cable technology, and in particular to a gradient-coordinated fire-resistant cable and its manufacturing method. Background Technology
[0002] Fire-resistant cables are core components ensuring the integrity of emergency power supply, fire-fighting linkage, and critical signal transmission lines in fire scenarios. They are widely used in high-rise buildings, rail transit, medical buildings, data centers, and other fields with stringent fire safety requirements. Currently, mainstream fire-resistant cables generally adopt a single fire-resistant mode, with core technologies mainly falling into two categories: one is an inorganic fire-resistant structure wrapped with mica tape, which has become the industry mainstream solution due to the high melting point and insulation properties of mica; the other is an organic-inorganic conversion fire-resistant structure extruded with high-molecular materials such as ceramicized silicone rubber and ceramicized polyolefins, which forms a rigid protective layer through high-temperature ceramicization phase transformation and has excellent processing performance. In addition, heavy-duty fire-resistant solutions such as rigid mineral-insulated cables are only used in a few extreme and special scenarios and have not achieved widespread adoption.
[0003] With the continuous upgrading of global fire safety standards, international standards such as BS EN 50200:2015 have imposed more stringent composite operating condition testing requirements on fire-resistant cables. The PH120 rating requires cables to maintain line integrity for 120 minutes under conditions of 842°C flame environment, periodic mechanical impact, and continuous loading of rated voltage, simulating the extreme conditions of building component collapse in a real fire. Faced with this high level of testing requirements, the inherent defects of existing single fire resistance modes are becoming increasingly apparent, manifesting in the following four technical shortcomings: First, pure metal wire braiding reinforcement poses a dual risk of thermal conductivity and short circuit. To improve high-temperature mechanical properties, existing fire-resistant cables mostly use pure stainless steel wire braiding as the reinforcement layer. Although it can provide sufficient radial clamping force, the high thermal conductivity of metal materials will rapidly conduct heat to the internal conductor in an 842℃ flame, accelerating the degradation of the insulation layer performance. At the same time, in high-voltage line integrity tests, if the outer ceramic shell is partially broken, the exposed metal wires are prone to contact with the internal conductor, causing a short circuit, resulting in insufficient dielectric safety.
[0004] Secondly, pure glass fiber braided reinforcement suffers from high-temperature softening and structural collapse. To avoid the thermal conductivity defects of metal braiding, some solutions use pure glass fiber braided reinforcement layers. Although it has the advantages of insulation and heat insulation, the softening point of commonly used E-glass fiber is about 830℃, which is close to the test temperature of 842℃. The tensile strength retention rate at high temperatures is less than 20%, which cannot provide the radial support force required for mechanical impact testing. After the ceramic shell breaks, the braided layer is prone to overall loosening and collapse, directly leading to circuit breakage.
[0005] Third, a single ceramicized layer carries the risk of through-cracks caused by thermal stress concentration. Existing ceramicized refractory schemes mostly adopt a single-layer structure design. During the rapid heating process to 842℃, the outer layer of the ceramic layer has already completed ceramicization and embrittlement, while the inner layer is still in a thermoplastic state. The asynchronous phase transformation between the inner and outer layers causes thermal stress concentration, which can easily lead to through-cracks in the ceramic shell. Flames and molten material can directly invade the conductor area along the cracks, causing circuit failure.
[0006] Fourth, gas-generating oxygen barriers suffer from high-temperature bulging and damage. Traditional oxygen barriers often use decomposition-generating fillers such as aluminum hydroxide and magnesium hydroxide, which release water vapor or inert gas through high-temperature decomposition to achieve oxygen isolation and flame retardancy. However, in a closed flame test environment, the large amount of gas generated by decomposition can easily cause interlayer bulging and cracking, which in turn damages the compactness of the refractory structure and becomes a channel for flame intrusion.
[0007] In addition to the four core defects mentioned above, existing fire-resistant cables also generally suffer from performance inconsistencies and insufficient adaptability to various application scenarios. Regarding flexibility and high-temperature mechanical properties, most products use hard copper conductors to ensure high-temperature structural strength, resulting in poor cable bending performance and making them unsuitable for installations in confined spaces or repeated bending. If soft copper conductors are used directly to improve flexibility, the conductor's mechanical strength decays too quickly at high temperatures, making it prone to breakage under mechanical impact. As for multi-core cable compatibility, the gaps between the cores create channels for flame spread and heat conduction. Mechanical impact can cause the cores to squeeze against each other, leading to localized structural collapse. Current technology lacks a systematic fire-resistant design for multi-core applications, resulting in insufficient overall fire-resistant reliability.
[0008] To address the aforementioned technical challenges, the industry has explored improvements in multiple directions. In the field of refractory structures, some solutions propose using multiple layers of refractory materials with different ceramization temperatures, attempting to improve the fire resistance limit through stacked multi-layer structures. In the field of reinforced structures, some technologies attempt to use a combination of metals and non-metals for reinforcement, aiming to combine the performance advantages of both types of materials. However, these improvements have not yet broken through the core bottleneck of the existing single refractory mode, and there are still many intractable technical problems: it is difficult to balance the mechanical properties and thermal insulation properties of the reinforced structure; the ceramicized structure is prone to cracking due to thermal stress concentration; the oxygen barrier layer is prone to bulging and damage; there is a contradiction between room temperature flexibility and high temperature mechanical properties; and there is a lack of systematic refractory design for multi-core scenarios.
[0009] Therefore, it is necessary to develop a new type of fire-resistant cable technology that can simultaneously take into account multiple dimensions of performance in order to reliably meet the requirements of high-grade fire-resistant line integrity. Summary of the Invention
[0010] Based on this, the purpose of the present invention is to provide a gradient-coordinated fire-resistant cable and its manufacturing method, which has the advantages of gradient sequential fire protection, strong structural stability, excellent high-temperature insulation performance, and reliable interlayer bonding.
[0011] A gradient-coordinated fire-resistant cable core, characterized in that: from the inside out, it comprises a conductor, a composite fire-resistant insulation layer, a first ceramicized layer, an oxygen barrier layer, a ceramicized adhesive layer, a braided reinforcement layer, and a second ceramicized layer; The mixed-weave reinforcing layer is made of glass fiber and stainless steel wire in a 1:1 ply ratio, with a weaving density of not less than 95%; the glass fiber is glass fiber treated with a silane coupling agent. The ceramicized adhesive layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:1, with a thickness of 0.1 mm to 0.2 mm, and is pre-coated between the oxygen barrier layer and the hybrid reinforcement layer. The ceramization initiation temperature T1 of the first ceramization layer is 480℃~580℃, and the ceramization initiation temperature T2 of the second ceramization layer is 680℃~880℃, with T2 being 100℃~300℃ higher than T1.
[0012] Compared to existing technologies, this invention is based on the inherent phase change temperature characteristics and interlayer heat conduction laws of the materials of each functional layer. Through the ceramicization temperature gradient design of the first ceramicized layer and the second ceramicized layer, combined with the molten filling of the oxygen barrier layer, the interfacial bonding of the ceramicized adhesive layer, and the mechanical support of the glass fiber-steel wire hybrid reinforcement layer, the functions of each layer are activated sequentially and synergistically according to the temperature time sequence. The whole structure constructs a graded response refractory mechanism of "first bearing - then constraining - then repairing", which fundamentally improves the defects of traditional single-layer ceramicized structure such as thermal stress concentration and easy cracking and peeling.
[0013] In the initial bearing stage during the early stage of flame heating, the first ceramization layer, with its relatively low ceramization initiation temperature T1 of 480℃ to 580℃, is the first to reach the phase transformation conditions, completing the ceramization transformation and forming a rigid primary ceramic shell. This shell, on the one hand, rapidly establishes the first rigid fire-resistant barrier on the inner side, preventing the flame and heat from being conducted to the internal insulation layer; on the other hand, it provides a stable inner bearing substrate for the oxygen barrier layer that subsequently enters the molten state, preventing structural damage such as loss, bulging, and flow of the oxygen barrier layer due to lack of support after high-temperature melting, thus providing a structural foundation for the stable performance of the subsequent oxygen barrier function. As the temperature continues to rise and enters the oxygen barrier confinement stage, the oxygen barrier layer enters its melting temperature range. Since its melting time is later than that of the first ceramization layer, a rigid ceramic shell has already formed on the inner side, and a mixed-woven reinforcement layer with a weave density of not less than 95% forms a confinement on the outer side. The molten oxygen barrier layer is confined within the space between the two layers and fully spreads, forming a continuous and dense vitreous oxygen barrier film. This membrane can fill the micropores and grain boundary gaps of the first ceramic shell, blocking oxygen from penetrating into the cable and inhibiting the thermal oxidation and degradation of the internal materials; it can also act as a flexible buffer layer to absorb some of the interlayer thermal stress, alleviate the interlayer mismatch caused by the difference in thermal expansion coefficients between different materials, and improve the stability of the interface bonding.
[0014] When the temperature rises further to the high-temperature repair stage, the second ceramicized layer reaches its ceramicization initiation temperature T2 and completes the ceramicization phase transition. T2 maintains a temperature gradient of 100℃ to 300℃ with T1, ensuring its response time is later than the inner two layers. This stage utilizes the volume expansion effect accompanying the ceramicization phase transition to automatically seal and repair microcracks and minor gaps in the outer ceramic shell caused by high-temperature thermal stress and periodic mechanical impact, improving the overall integrity of the ceramic shell. Simultaneously, a continuous secondary fire-resistant barrier is formed on the outside of the hybrid reinforcement layer, which, together with the inner first ceramicized layer and the intermediate hybrid reinforcement layer, constitutes a multi-layered protective structure, further preventing heat and flames from penetrating into the cable and slowing the internal temperature rise rate.
[0015] Throughout the entire heating response process, the hybrid reinforcement layer and the ceramicized bonding layer play a crucial structural role. The hybrid reinforcement layer is composed of glass fiber treated with a silane coupling agent and stainless steel wire in a 1:1 strand ratio. The glass fiber component, with its low thermal conductivity, acts as a thermal insulation buffer, delaying heat conduction inward. The stainless steel wire component provides a high-strength mechanical skeleton, providing stable radial clamping force to each ceramicized layer throughout the process, inhibiting cracking, peeling, and interlayer misalignment of the ceramic shell at high temperatures. The ceramicized bonding layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:1, with a thickness of 0.1 mm to 0.2 mm. It is pre-coated between the oxygen barrier layer and the hybrid reinforcement layer. At high temperatures, it can undergo interfacial sintering bonding with the materials on both sides, effectively inhibiting slippage and separation between layers, ensuring the orderly execution of functions at each stage and the overall stability of the structure. In summary, through the above-mentioned temperature gradient design and sequential functional division, each functional layer is not a simple structural stack, but rather undertakes the functions of structural load-bearing, oxygen-barrier sealing, buffer reinforcement, and crack repair in turn at different temperature stages. Each link cooperates with each other and progresses layer by layer to form a synergistic and efficient overall fire-resistant system, which can effectively improve the structural integrity of the ceramic shell of the cable and the reliability of the line insulation under the coupling conditions of high temperature and mechanical impact.
[0016] Furthermore, the conductor is a Class 5 or Class 6 soft copper stranded conductor. These conductors combine excellent conductivity with bending flexibility, making them suitable for complex laying scenarios.
[0017] Furthermore, the oxygen barrier layer is a composite extruded layer of low-melting-point glass powder and ceramizable filler, which is melted at 600℃~800℃ to form a dense vitreous oxygen barrier film. Matching the phase transition sequence of the two ceramizable layers achieves interface sealing and oxygen barrier thermal insulation.
[0018] Furthermore, the composite fire-resistant insulation layer has a double-layer composite structure, with an inner layer of mica glass tape and an outer layer of nano-Al2O3 / micron-sized mica-modified polyimide (PI) composite film. The double layers work synergistically to delay the temperature rise on the conductor side and enhance the insulation protection capability on the conductor side.
[0019] Furthermore, the present invention also provides a single-core gradient-coordinated fire-resistant cable, comprising the aforementioned gradient-coordinated fire-resistant cable core and an outer sheath layer disposed outside the core.
[0020] Furthermore, the outer sheath layer is extruded from a ceramicized low-smoke halogen-free flame-retardant material.
[0021] Furthermore, the present invention also provides a method for preparing the above-mentioned single-core gradient-coordinated fire-resistant cable, comprising the following steps: S1: Preparation of conductor; S2: A composite fire-resistant insulating layer and a first ceramicized layer are sequentially formed on the surface of the conductor, and the ceramicization initiation temperature T1 of the first ceramicized layer is controlled to be 480℃~580℃; S3: An oxygen barrier layer is formed on the surface of the first ceramicized layer; S4: A ceramicized adhesive layer is pre-coated on the surface of the oxygen barrier layer and dried. The ceramicized adhesive layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:1. S5: Glass fibers treated with silane coupling agent are mixed with stainless steel wires at a ply ratio of 1:1 to form a mixed reinforcing layer with a weaving density of not less than 95% on the surface of the ceramicized bonding layer. S6: A second ceramicized layer is formed on the surface of the hybrid reinforcement layer, and the ceramicization initiation temperature T2 of the second ceramicized layer is controlled to be 680℃~880℃, and T2 is 100℃~300℃ higher than T1; S7: An outer sheath layer is formed on the surface of the second ceramicized layer, thus obtaining the single-core gradient-coordinated fire-resistant cable.
[0022] Furthermore, the present invention also provides a multi-core gradient-coordinated fire-resistant cable, comprising a core unit and a fire-resistant wrapping layer and an outer sheath layer sequentially covering the core unit; the core unit is formed by stranding at least two gradient-coordinated fire-resistant cable cores as described in any one of claims 1 to 7 into a cable, and the gap between the cable cores is filled with ceramic fire-resistant filler strips.
[0023] Furthermore, the ceramicized refractory filler strip is extruded from ceramicized silicone rubber or ceramicized low-smoke halogen-free polyolefin material, with a fan-shaped or circular cross-section and a filling rate of not less than 90%.
[0024] Furthermore, the present invention also provides a method for manufacturing the above-mentioned multi-core gradient coordinated fire-resistant cable, comprising the following steps: S1: Preparation of conductor; S2: A composite fire-resistant insulating layer and a first ceramicized layer are sequentially formed on the surface of the conductor, and the ceramicization initiation temperature T1 of the first ceramicized layer is controlled to be 480℃~580℃; S3: An oxygen barrier layer is formed on the surface of the first ceramicized layer; S4: A ceramicized adhesive layer is pre-coated on the surface of the oxygen barrier layer and dried. The ceramicized adhesive layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:1. S5: Glass fibers treated with silane coupling agent are mixed with stainless steel wires at a ply ratio of 1:1 to form a mixed reinforcing layer with a weaving density of not less than 95% on the surface of the ceramicized bonding layer. S6: A second ceramicized layer is formed on the surface of the hybrid reinforcement layer. The ceramicization initiation temperature T2 of the second ceramicized layer is controlled to be 680℃~880℃, and T2 is 100℃~300℃ higher than T1, so as to obtain a single gradient-coordinated fire-resistant cable core. S7: Twist at least two of the gradient-coordinated fire-resistant cable cores together to form a core unit; S8: The gap between the cable cores of the wire core unit is filled with ceramicized fire-resistant filler strips; S9: A fire-resistant wrapping layer is formed by wrapping around the outside of the core unit; S10: An outer sheath layer is formed outside the fire-resistant wrapping layer, thus obtaining the multi-core gradient coordinated fire-resistant cable.
[0025] To better understand and implement this invention, the following detailed description is provided in conjunction with the accompanying drawings. Attached Figure Description
[0026] Figure 1 This is a schematic diagram of the structure of the single-core gradient-coordinated fire-resistant cable in Example 1; Figure 2 This is a schematic diagram of the hybrid reinforcement layer in the gradient-coordinated fire-resistant cable of the present invention; Figure 3 This is a schematic diagram of the structure of the multi-core gradient coordinated fire-resistant cable in Example 2; Figure 4 This is a schematic diagram comparing the integrity of the ceramic shell after testing each group of cables. Detailed Implementation
[0027] To facilitate understanding of the present invention, it will be described more fully below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein.
[0028] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to limit the embodiments of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise. It should also be understood that the term “and / or” as used herein refers to and includes any or all possible combinations of one or more of the associated listed items.
[0029] The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with this application. In the description of this application, it should be understood that the terms "first," "second," "third," etc., are used only to distinguish similar objects and are not necessarily used to describe a specific order or sequence, nor should they be construed as indicating or implying relative importance. Those skilled in the art can understand the specific meaning of the above terms in this application according to the specific circumstances.
[0030] The experimental methods in the following examples or comparative examples, unless otherwise specified, are generally performed under conventional conditions in the art or as recommended by the manufacturer; the raw materials and reagents used, unless otherwise specified, are all commercially available from the conventional market.
[0031] Example 1 A single-core gradient-coordinated fire-resistant cable, such as Figure 1 As shown, from the inside out, it includes conductor 1, composite fire-resistant insulation layer 2, first ceramicized layer 3, oxygen barrier layer 4, ceramicized adhesive layer 5, mixed reinforcement layer 6, second ceramicized layer 7, and outer sheath layer 8. The specific structure and parameters of each layer are as follows: Conductor 1 is a Class 5 soft copper stranded conductor with a nominal cross-sectional area of 2.5 mm². It is made of soft copper wire that meets the requirements of Class 5 conductors in GB / T3956-2008. Its DC resistance meets the requirements of the standard, ensuring the flexibility and bending performance of the cable.
[0032] Conductor 1 can also be a Class 6 soft copper stranded conductor. Composite refractory insulation layer 2 adopts a double-layer composite structure. The inner layer is a mica glass tape with a thickness of 0.12 mm and an overlap wrapping rate of 50%, serving as a high-temperature inorganic skeleton; the outer layer is a nano-Al2O3 / micron mica-modified polyimide (PI) composite film with a thickness of 0.06 mm, with double-layer reverse overlap wrapping and an overlap rate of 55%. After high-temperature sintering, the PI matrix carbonizes, and the nano-Al2O3 and mica powder form a dense sintered layer on the surface of the glass tape skeleton.
[0033] The first ceramicized layer 3 is made of ceramicizable low-smoke halogen-free polyolefin through extrusion, with a thickness of 0.8 mm and a ceramicization initiation temperature T1 = 550℃. This layer preferentially ceramicizes under flame conditions, forming a primary rigid protective shell, providing a load-bearing substrate for the outer oxygen barrier layer 4.
[0034] The oxygen barrier layer 4 is made of low-melting-point glass powder and ceramizable filler through composite extrusion, with a thickness of 0.4 mm. The low-melting-point glass powder can be a commercially available product, such as one with an initial melting temperature of 550℃ and a full melting temperature of 700℃, forming a continuous glassy film within the temperature range of 600℃ to 800℃. Since the first ceramization layer 3 has already completed ceramization and formed a rigid shell before the oxygen barrier layer 4, the molten oxygen barrier film is constrained between the ceramic shell and the hybrid reinforcement layer 6, preventing leakage or bulging.
[0035] The ceramicized bonding layer 5 is pre-coated with low melting point glass powder and silica sol in a mass ratio of 4:1, with a thickness of 0.15 mm. After pre-coating, it is dried at 100°C for 8 min. It is used to sinter and bond the mixed reinforcement layer 6 with the oxygen barrier layer 4 and the first ceramicized layer 3 to prevent high-temperature slippage.
[0036] Hybrid reinforcement layer 6, its structure is as follows Figure 2 As shown, the yarn is made by plying and weaving E-glass fiber treated with a silane coupling agent and 304 stainless steel wire in a 1:1 ratio. This means that each spindle of the braiding machine simultaneously releases one stainless steel wire and one glass fiber strand to form one braided yarn, ensuring a strict 1:1 ratio of the two in the braided layer and a braiding density of 96%. The E-glass fiber strand diameter is 0.3 mm, and the 304 stainless steel wire diameter is 0.1 mm. During plying and weaving, the steel wire tension is controlled at 5 N, and the glass fiber tension at 3 N. Actual production verification shows that this tension window ensures that the 0.1 mm diameter stainless steel wire is within a safe breaking force range, preventing wire breakage, while also guaranteeing the uniformity of the braided layer and a braiding density of over 95%. The stainless steel wire provides core radial clamping force and skeletal support, while the glass fiber fills the gaps between the steel wires to form a heat-insulating buffer layer and utilizes its rough surface to enhance the mechanical interlocking with the ceramic shell.
[0037] The second ceramicized layer 7 consists of two layers of ceramicized silicone rubber tape wrapped around it. The ceramicization initiation temperature T2 = 800℃, forming a temperature gradient of 250℃ with T1. When the outer ceramic shell develops microcracks under flame impact, the second ceramicized layer 7 further ceramicizes during the continuous heating process, utilizing the volume expansion effect during the ceramicization phase transition to self-repair the microcracks. At the same time, the inner ceramicized first ceramicized layer 3 acts as a rigid load-bearing shell, forming a secondary fire-resistant barrier together with the mixed reinforcement layer 6 to prevent flames from entering along the cracks.
[0038] The outer sheath layer 8 is made of ceramicized low-smoke halogen-free flame-retardant material extruded with a thickness of 1.2mm. It provides flame retardancy and mechanical protection at room temperature, and forms the outermost thermal barrier by self-ceramization at high temperature.
[0039] The single-core gradient-coordinated fire-resistant cable of this embodiment is prepared by the following method: S1: A Class 5 soft copper stranded conductor is used as conductor 1. The nominal cross-sectional area of the conductor is 2.5 mm². It is made of soft copper wire that meets the requirements of Class 5 conductor in GB / T3956-2008. The DC resistance meets the requirements of this standard.
[0040] S2: A mica glass tape is overlapped and wrapped around the surface of conductor 1 with an overlap rate of 50% to form an inner insulation layer; then, a nano-Al2O3 / micron mica-modified polyimide (PI) composite film is double-layered and overlapped on the surface of the inner insulation layer with an overlap rate of 55% to form a composite fire-resistant insulation layer 2; wherein the thickness of the mica glass tape is 0.12mm and the thickness of the composite film is 0.06mm.
[0041] S3: Ceramicizable low-smoke halogen-free polyolefin is extruded onto the surface of the composite refractory insulation layer 2 to form the first ceramicized layer 3. The ceramicization initiation temperature T1 is controlled at 550℃ and the extrusion thickness is 0.8mm.
[0042] S4: An oxygen barrier layer 4, composed of low-melting-point glass powder and ceramicizable filler, is extruded onto the surface of the first ceramicized layer 3, with a thickness of 0.4 mm; the low-melting-point glass powder has an initial melting temperature of 550°C and a full melting temperature of 700°C, and can form a continuous glassy film in the temperature range of 600°C to 800°C.
[0043] S5: A ceramicized adhesive layer 5 with a thickness of 0.15 mm is pre-coated on the surface of the oxygen barrier layer 4. The ceramicized adhesive layer 5 is composed of low melting point glass powder and silica sol in a mass ratio of 4:1. After pre-coating, it is dried at 100℃ for 8 minutes.
[0044] S6: E-glass fiber treated with silane coupling agent and 304 stainless steel wire are stranded together at a ratio of 1:1, and the tension of the steel wire is controlled at 5N and the tension of the glass fiber is 3N. The strands are then mixed and woven on the surface of the ceramicized bonding layer 5 to form a mixed-woven reinforcing layer 6 with a weaving density of 96%. The diameter of the E-glass fiber strands is 0.3mm and the diameter of the 304 stainless steel wire is 0.1mm.
[0045] S7: Two layers of ceramicized silicone rubber tape are wrapped around the surface of the hybrid reinforcing layer 6 to form the second ceramicized layer 7. The ceramicization initiation temperature T2 is controlled at 800℃, forming a temperature gradient of 250℃ with T1.
[0046] S8: Extruding ceramic low-smoke halogen-free flame-retardant material onto the surface of the second ceramic layer 7 forms the outer sheath layer 8 with an extrusion thickness of 1.2mm, thus completing the manufacturing of the single-core cable.
[0047] Example 2 A multi-core gradient-coordinated fire-resistant cable, such as Figure 3 As shown, from the inside out, it includes a core unit, a ceramicized refractory filler strip 9, a refractory wrapping layer 10, and an outer sheath layer 8.
[0048] The specific structure and parameters of each part of the multi-core gradient coordinated fire-resistant cable in this embodiment are as follows: The core unit comprises three cores, each employing the same single-core gradient synergistic fire-resistant structure as in Example 1. From the inside out, it consists of a conductor 1, a composite fire-resistant insulation layer 2, a first ceramicized layer 3, an oxygen barrier layer 4, a ceramicized adhesive layer 5, a braided reinforcing layer 6, and a second ceramicized layer 7. Each core independently possesses complete gradient synergistic fire-resistant capabilities, forming an intrinsic "fire-resistant unit."
[0049] The conductor 1 of the core is a Class 5 soft copper stranded conductor with a specification of 2.5mm². The materials, thicknesses, and process parameters of the composite fire-resistant insulation layer 2, the first ceramicized layer 3, the oxygen barrier layer 4, the ceramicized adhesive layer 5, the mixed braided reinforcing layer 6, and the second ceramicized layer 7 are all consistent with those of Example 1. The three cores are concentrically stranded into a cable with a stranding pitch of 110mm, and the stranding direction is right-handed. The gaps between the cable cores are filled with ceramicized fire-resistant filler strips 9. The ceramicized fire-resistant filler strips 9 are extruded from ceramicized silicone rubber or ceramicized low-smoke halogen-free polyolefin material, with a fan-shaped or circular cross-section and a filling rate of not less than 90%.
[0050] Under the action of an 842℃ flame, the ceramicized fire-resistant filler strip 9 is ceramicized before or simultaneously with the outer sheath layer 8, forming a dense solid filler that blocks the path for the spread of flame and high-temperature gas along the gap between the cable cores, while providing additional radial support to prevent the cores from being squeezed and deformed at high temperatures.
[0051] Fire-resistant wrapping layer 10: After cabling, a mica glass tape or ceramicized silicone rubber tape is wrapped around the outside of the cable core with a thickness of 0.2mm to 0.3mm and an overlap rate of not less than 30%. It serves as a secondary fire-resistant barrier for the overall structure to prevent flames from directly invading the cable core when the outer sheath layer 8 is partially damaged.
[0052] Outer sheath layer 8: Made of ceramicized low-smoke halogen-free flame-retardant material extruded, with a thickness of 1.5mm to 2.0mm. It provides flame retardancy, mechanical protection and environmental resistance at room temperature, and forms the outermost overall thermal barrier at high temperature through self-ceramization.
[0053] The multi-core gradient-coordinated fire-resistant cable of this embodiment is manufactured by the following method: S1: A Class 5 soft copper stranded conductor is used as conductor 1. The nominal cross-sectional area of the conductor is 2.5 mm². It is made of soft copper wire that meets the requirements of Class 5 conductor in GB / T3956-2008. The DC resistance meets the requirements of this standard.
[0054] S2: A mica glass tape is overlapped and wrapped around the surface of conductor 1 with an overlap rate of 50% to form an inner insulation layer; then, a nano-Al2O3 / micron mica-modified polyimide (PI) composite film is double-layered and overlapped on the surface of the inner insulation layer with an overlap rate of 55% to form a composite fire-resistant insulation layer 2; wherein the thickness of the mica glass tape is 0.12mm and the thickness of the composite film is 0.06mm.
[0055] S3: Ceramicizable low-smoke halogen-free polyolefin is extruded onto the surface of the composite refractory insulation layer 2 to form the first ceramicized layer 3. The ceramicization initiation temperature T1 is controlled at 550℃ and the extrusion thickness is 0.8mm.
[0056] S4: An oxygen barrier layer 4, composed of low-melting-point glass powder and ceramicizable filler, is extruded onto the surface of the first ceramicized layer 3, with a thickness of 0.4 mm; the low-melting-point glass powder has an initial melting temperature of 550°C and a full melting temperature of 700°C, and can form a continuous glassy film in the temperature range of 600°C to 800°C.
[0057] S5: A ceramicized adhesive layer 5 with a thickness of 0.15 mm is pre-coated on the surface of the oxygen barrier layer 4. The ceramicized adhesive layer 5 is composed of low melting point glass powder and silica sol in a mass ratio of 4:1. After pre-coating, it is dried at 100℃ for 8 minutes.
[0058] S6: E-glass fiber treated with silane coupling agent and 304 stainless steel wire are stranded together at a ratio of 1:1, and the tension of the steel wire is controlled at 5N and the tension of the glass fiber is 3N. The strands are then mixed and woven on the surface of the ceramicized bonding layer 5 to form a mixed-woven reinforcing layer 6 with a weaving density of 96%. The diameter of the E-glass fiber strands is 0.3mm and the diameter of the 304 stainless steel wire is 0.1mm.
[0059] S7: Two layers of ceramicized silicone rubber tape are wrapped around the surface of the hybrid reinforcing layer 6 to form the second ceramicized layer 7. The ceramicization initiation temperature T2 is controlled at 800℃, forming a temperature gradient of 250℃ with T1, to obtain the wire core.
[0060] S8: Take three wire cores that have completed steps S1 to S7, and concentrically twist them into a cable with a twisting pitch of 110mm, with the twisting direction being right-hand.
[0061] S9: The gap between the cable cores is filled with ceramicized fire-resistant filler strips 9, with a filling rate of not less than 90%; the ceramicized fire-resistant filler strips 9 are made of ceramicized silicone rubber or ceramicized low-smoke halogen-free polyolefin material extruded, and the cross section is fan-shaped or circular.
[0062] S10: After cabling, a fire-resistant wrapping layer 10 is wrapped around the outside of the cable core, with an overlap rate of not less than 30%; the fire-resistant wrapping layer 10 is a mica glass tape or a ceramicized silicone rubber tape with a thickness of 0.2mm to 0.3mm.
[0063] S11: Ceramicized low-smoke halogen-free flame-retardant material is extruded onto the surface of the fire-resistant wrapping layer 10 to form the outer sheath layer 8. The extrusion thickness is 1.5mm to 2.0mm, thus completing the manufacturing of the multi-core cable.
[0064] To verify the actual effect of the present invention, the following comparative examples are set up.
[0065] Comparative Example 1 The difference between a single-core fire-resistant cable and the single-core gradient synergistic fire-resistant cable of Example 1 is that the braided reinforcement layer of this comparative fire-resistant cable is made of pure 304 stainless steel wire with a wire diameter of 0.1 mm and a braiding density of 96%.
[0066] The remaining layer structure is the same as in Example 1.
[0067] Comparative Example 2 The difference between a single-core fire-resistant cable and the single-core gradient synergistic fire-resistant cable of Example 1 is that the braided reinforcement layer of this comparative fire-resistant cable is a pure E-glass fiber braided reinforcement layer with a braiding density of 96%.
[0068] The remaining layer structure is the same as in Example 1.
[0069] Comparative Example 3 A single-core fire-resistant cable differs from the single-core gradient synergistic fire-resistant cable of Example 1 in that the fire-resistant cable of this comparative example retains the mixed braided reinforcing layer (strand ratio 1:1, braiding density 96%) and the ceramicized adhesive layer, and replaces the first ceramicized layer and the second ceramicized layer with a single layer of ceramicized silicone rubber with a thickness of 2.0 mm and a ceramicization initiation temperature of about 650°C; the structure of the remaining layers is the same as that of Example 1.
[0070] The ceramic layer in this comparative example has a ceramicization temperature that is located in the temperature gap between the upper limit of the first ceramicization layer (580°C) and the lower limit of the second ceramicization layer (680°C) of this invention. This temperature gap does not trigger the inner ceramicization bearing mechanism, nor does it reach the critical point of the outer high-temperature repair. This temperature gap can objectively reflect the performance limit of the gradient-free design and avoid falling into the temperature protection range of any ceramicization layer of this invention.
[0071] Comparative Example 4 A multi-core fire-resistant cable differs from the multi-core gradient synergistic fire-resistant cable of Example 2 in that the mixed braided reinforcing layer of each core in this comparative fire-resistant cable is replaced with a pure 304 stainless steel wire braided structure, and no ceramicized fire-resistant filler strips are installed after cabling; the gaps between the cable cores are filled with ordinary PP rope. The remaining structure is the same as in Example 2.
[0072] Performance testing Test subjects: Fire-resistant cables of Examples 1-2 and Comparative Examples 1-4 of this invention.
[0073] Test conditions: Each group of cables was placed in a muffle furnace and continuously burned at 842℃ for 120 minutes; during the burning process, a falling ball impact was applied every 5 minutes, with the impact condition being a 1kg steel ball falling freely from a height of 0.5m; throughout the test, a 1000V DC voltage was applied to the samples, and the integrity of the circuit was monitored in real time. The test indicators represent the observation and evaluation of the cable's fire resistance performance from different dimensions during or after the test.
[0074] The braided layer impact strength retention rate was obtained by mechanically evaluating the remaining braided layer 120 minutes after the test. It was verified that when the retention rate is ≥82%, the braided layer can provide sufficient radial clamping force to meet the EN50200 mechanical impact test requirements; when the retention rate is <55%, the risk of cable structural failure increases sharply, easily accompanied by structural collapse or insulation breakdown.
[0075] The thermal insulation temperature difference between the flame side and the conductor side was obtained by monitoring the radial temperature difference of the cable after 120 minutes of testing. It should be noted that the thermal insulation temperature difference is only one dimension of fire resistance performance. A high single temperature difference value does not mean that the overall test is passed. If the braided layer softens and collapses at high temperature, even if the thermal insulation performance is excellent, the overall cable structure will still fail.
[0076] The 1000V high-voltage insulation test is monitored in real time throughout the entire test process. It is the core qualification standard for BS EN 50200PH120 level, requiring the cable to not break down or short-circuit during the entire 120-minute test and to continuously maintain the integrity of the line.
[0077] The integrity of the ceramic shell is evaluated by visual inspection after the test. The criteria for acceptance are that the ceramic shell structure is intact and there are no through cracks; the unacceptable conditions include the ceramic shell being broken, falling off, or having through cracks.
[0078] The interlayer slippage was examined by dissecting the sample after the test. The pass / fail criterion was that there was no slippage or separation between the structural layers; the fail-fail criterion was that the interlayers separated or detached.
[0079] The multi-core gap propagation test only applies to multi-core cable samples. After the test, the samples are dissected and inspected. The pass / fail criterion is that the gap between the cable cores is effectively blocked by the ceramic filler strip and there is no flame propagation along the gap. The failure is that the gap forms an erosion channel, which in turn causes a short circuit between the cores.
[0080] Test results: See Table 1 below and Figure 4 As shown.
[0081] Table 1 Test Project Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Example 1 Example 2 Impact strength retention rate of the braided layer (after 120 minutes) 68% 12% (structural collapse) 55% 68% (partial structural collapse, accompanied by electrical short circuit) ≥82% ≥82% Temperature difference between the flame side and the conductor side at 120 min 45℃ 165℃ (but the structure has failed) 50℃ 48℃ ≥135℃ ≥135℃ 1000V high-voltage insulation test (120min) Short circuit Not approved Failed (through crack appeared in the ceramic shell after 120 minutes, and the 1000V high-voltage test failed). Breakdown short circuit (short circuit between wire cores) pass pass Ceramic shell integrity (visual inspection) Partially broken, not peeled off The whole thing broke and fell off. Through crack Localized fragmentation and gap collapse Complete, without through cracks Complete, without through cracks Interlayer slip none Severe slippage Slight slippage none No slippage No slippage Multi-core gap propagation — — — Flame penetrates along the gap, causing a short circuit between the wire cores. — The gaps are blocked by ceramic filler strips, preventing propagation. As can be seen from the test results in Table 1, the overall fire resistance performance of the gradient synergistic fire-resistant cable of the present invention under high temperature mechanical impact conditions is significantly better than that of the comparative sample. It can stably meet the line integrity requirements of BS EN 50200PH120 level, while the comparative samples all showed different forms of performance failure due to their own structural defects.
[0082] Comparative Example 1 uses a pure 304 stainless steel wire braided reinforcement layer. The braided layer retains 68% of its impact strength. Although it has a certain radial support capacity, the high thermal conductivity of the metal material results in a thermal insulation temperature difference of only 45°C between the flame side and the conductor side, causing the internal conductor to heat up too quickly. At the same time, after the ceramic shell partially fractures under mechanical impact, the exposed stainless steel wire comes into contact with the internal conductor, causing a short circuit. This leads to a breakdown in the 1000V high-voltage insulation test, and the whole structure fails the fire resistance test. This demonstrates the inherent defect that pure metal reinforcement structures cannot simultaneously achieve both mechanical performance and dielectric safety.
[0083] Comparative Example 2 uses a pure E-glass fiber woven reinforcement layer, which has the best thermal insulation performance. The thermal insulation temperature difference between the flame side and the conductor side can reach 165℃. However, the E-glass fiber softens significantly at a high temperature of 842℃. After 120 minutes, the impact strength retention rate of the woven layer is only 12%. The overall structure of the woven layer collapses and cannot maintain the structural integrity of the ceramic shell. In the end, the ceramic shell breaks and falls off, the circuit loses protection and breaks, and the high-voltage insulation test fails. This reflects the problem that the high-temperature mechanical properties of the pure glass fiber reinforced structure are insufficient and it is difficult to withstand periodic mechanical impacts.
[0084] Comparative Example 3 uses a single-layer ceramicized structure without temperature gradient. Although it retains the braided reinforcement layer and the ceramicized bonding layer, the impact strength retention rate of its braided layer is only 55%, and the thermal insulation temperature difference between the flame side and the conductor side is only 50℃. Due to the asynchronous phase transformation of the inner and outer sides of the single-layer ceramicized structure during rapid heating, the thermal stress concentration causes through-cracks to form in the ceramic shell. The flame and molten material directly penetrate into the conductor area along the crack, resulting in breakdown in the high-voltage insulation test. This proves that a single ceramicized structure cannot effectively disperse thermal stress, and even with a composite reinforcement structure, the failure risk of through-cracks cannot be fundamentally solved.
[0085] Comparative Example 4 is a multi-core cable without ceramic fire-resistant filler strips. Each core adopts a pure steel wire braided reinforcement structure, and the impact strength retention rate of its braided layer is 68%. The thermal insulation temperature difference between the flame side and the conductor side is only 48℃. Under high temperature, the ordinary PP rope filler material decomposes and shrinks, and obvious ablation channels are formed in the gaps between the cable cores. The flame spreads rapidly along the gaps and causes short circuits between the cores. Finally, the overall structure collapses locally, verifying the technical shortcomings of multi-core cables that cannot form overall fire protection when they lack inter-core gap blocking mechanisms.
[0086] in addition, Figure 4This is a comparative schematic diagram showing the integrity of the ceramic shells of each group of samples after being burned at 842℃ for 120 minutes and subjected to periodic mechanical impact tests. In the single-core gradient-coordinated fire-resistant cable sample of this invention, the ceramic shell maintains a complete annular structure, with only minor surface cracks and no radial through-cracks. It maintains a dense and continuous protective form, effectively preventing flame and heat from penetrating the cable. In contrast, the pure steel wire braided reinforced sample of Comparative Example 1 showed localized fracture of its ceramic shell, breaking it into two sections. Although not completely detached from the cable body, it formed a significant structural gap, losing its circumferential continuous protective capability. In contrast, the pure glass fiber braided reinforced sample of Comparative Example 2 showed overall fracture and detachment of its ceramic shell, with the broken ceramic shell exhibiting fragmented characteristics. The scattered fragments completely lost the continuous protective function of the shell, and the internal structure of the cable was directly exposed to the flame environment. In Comparative Example 3, the ceramic shell of the ungraded ceramic sample showed radial through cracks. The cracks extended from the outside to the inside of the ceramic shell, forming a through flame intrusion channel, which could not achieve effective fire and heat insulation. In Comparative Example 4, the multi-core unfilled sample showed that although the ceramic shell of the single core was locally attached, the gap between the cores formed an obvious ablation channel due to the lack of a ceramic fire-resistant filling structure. Structural collapse occurred at the gap, and the flame could spread along the gap inside the core, eventually leading to short circuit failure between the cores.
[0087] The embodiments described above are merely examples of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and the present invention also intends to include these modifications and variations.
Claims
1. A gradient-coordinated fire-resistant cable core, characterized in that: From the inside out, it includes a conductor, a composite fire-resistant insulation layer, a first ceramicized layer, an oxygen barrier layer, a ceramicized adhesive layer, a mixed-strength reinforcement layer, and a second ceramicized layer. The mixed-weave reinforcing layer is made of glass fiber and stainless steel wire in a 1:1 ply ratio, with a weaving density of not less than 95%; the glass fiber is glass fiber treated with a silane coupling agent. The ceramicized adhesive layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:1, with a thickness of 0.1 mm to 0.2 mm, and is pre-coated between the oxygen barrier layer and the hybrid reinforcement layer. The ceramization initiation temperature T1 of the first ceramization layer is 480℃~580℃, and the ceramization initiation temperature T2 of the second ceramization layer is 680℃~880℃, with T2 being 100℃~300℃ higher than T1.
2. The gradient-coordinated fire-resistant cable core according to claim 1, characterized in that: The conductor is a Class 5 or Class 6 soft copper stranded conductor.
3. The gradient-coordinated fire-resistant cable core according to claim 1, characterized in that: The oxygen barrier layer is a composite extruded layer of low-melting-point glass powder and ceramicizable filler, which is melted at 600℃~800℃ to form a dense glassy oxygen barrier film.
4. The gradient-coordinated fire-resistant cable core according to claim 1, characterized in that: The composite fire-resistant insulation layer has a double-layer composite structure, with the inner layer being a mica glass tape and the outer layer being a nano-Al2O3 / micron mica-modified polyimide (PI) composite film.
5. A single-core gradient-coordinated fire-resistant cable, characterized in that: It includes the gradient-coordinated fire-resistant cable core as described in any one of claims 1 to 4 and the outer sheath layer disposed outside the core.
6. A single-core gradient-coordinated fire-resistant cable according to claim 5, characterized in that: The outer sheath is extruded from a ceramicized low-smoke halogen-free flame-retardant material.
7. A method for manufacturing a single-core gradient-coordinated fire-resistant cable according to any one of claims 5 to 6, characterized in that, Includes the following steps: S1: Preparation of conductor; S2: A composite fire-resistant insulating layer and a first ceramicized layer are sequentially formed on the surface of the conductor, and the ceramicization initiation temperature T1 of the first ceramicized layer is controlled to be 480℃~580℃; S3: An oxygen barrier layer is formed on the surface of the first ceramicized layer; S4: A ceramicized adhesive layer is pre-coated on the surface of the oxygen barrier layer and dried. The ceramicized adhesive layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:
1. S5: Glass fibers treated with silane coupling agent are mixed with stainless steel wires at a ply ratio of 1:1 to form a mixed reinforcing layer with a weaving density of not less than 95% on the surface of the ceramicized bonding layer. S6: A second ceramicized layer is formed on the surface of the hybrid reinforcement layer, and the ceramicization initiation temperature T2 of the second ceramicized layer is controlled to be 680℃~880℃, and T2 is 100℃~300℃ higher than T1; S7: An outer sheath layer is formed on the surface of the second ceramicized layer, thus obtaining the single-core gradient-coordinated fire-resistant cable.
8. A multi-core gradient-coordinated fire-resistant cable, characterized in that: It includes a core unit and a fire-resistant wrapping layer and an outer sheath layer that are sequentially wrapped around the core unit; the core unit is made of at least two gradient-coordinated fire-resistant cable cores as described in any one of claims 1 to 4 twisted into a cable, and the gap between the cable cores is filled with ceramic fire-resistant filler strips.
9. The multi-core gradient-coordinated fire-resistant cable according to claim 8, characterized in that: The ceramicized refractory filler strip is extruded from ceramicized silicone rubber or ceramicized low-smoke halogen-free polyolefin material, with a fan-shaped or circular cross-section and a filling rate of not less than 90%.
10. A method for manufacturing a multi-core gradient-coordinated fire-resistant cable according to any one of claims 8 to 9, characterized in that, Includes the following steps: S1: Preparation of conductor; S2: A composite fire-resistant insulating layer and a first ceramicized layer are sequentially formed on the surface of the conductor, and the ceramicization initiation temperature T1 of the first ceramicized layer is controlled to be 480℃~580℃; S3: An oxygen barrier layer is formed on the surface of the first ceramicized layer; S4: A ceramicized adhesive layer is pre-coated on the surface of the oxygen barrier layer and dried. The ceramicized adhesive layer is composed of low-melting-point glass powder and silica sol in a mass ratio of 3:1 to 5:
1. S5: Glass fibers treated with silane coupling agent are mixed with stainless steel wires at a ply ratio of 1:1 to form a mixed reinforcing layer with a weaving density of not less than 95% on the surface of the ceramicized bonding layer. S6: A second ceramicized layer is formed on the surface of the hybrid reinforcement layer. The ceramicization initiation temperature T2 of the second ceramicized layer is controlled to be 680℃~880℃, and T2 is 100℃~300℃ higher than T1, so as to obtain a single gradient-coordinated fire-resistant cable core. S7: Twist at least two of the gradient-coordinated fire-resistant cable cores together to form a core unit; S8: The gap between the cable cores of the wire core unit is filled with ceramicized fire-resistant filler strips; S9: A fire-resistant wrapping layer is formed by wrapping around the outside of the core unit; S10: An outer sheath layer is formed outside the fire-resistant wrapping layer, thus obtaining the multi-core gradient coordinated fire-resistant cable.
